قياس منحنيات (كثافة تيار- جهد) لتحديد متغيرات وكفاءة الخلية الشمسية السليكونية PIN (Latakia University Journal -Basic Sciences Series, 2014)
تقدم هذه الدراسة قياساً لخواص (فولت-أمبير) لخلية شمسية PIN مصنوعة من السيليسيوم اللابلوري أما الطبقة I  النقية فهي مصنوعة من خليط من السيليسيوم اللابلوري والمكروبلوري المهدرج وذلك من أجل شدات ضوئية مختلفة باستخدام لمبة هالوجين باستطاعة ، حيث قيست كثافة الضوء الوارد على الخلية بمقياس قدرة وكانت . تمّ الحصول وبشكل مباشر من المنحنيات الناتجة على المتغيرات الأساسية للخلية الشمسية وهي: كثافة تيار قصر الدارة  ، جهد الدارة المفتوحة ، عامل الامتلاء ، وكفاءة تحويل الطاقة الشمسية (المردود) . ومن أجل الحصول على متغيرات الخلية الشمسية مثل تيار الإشباع  وعامل المثالية  للديود والمقاومة التسلسلية ومقاومة التوازي  وتيار الإضاءة  تمت ملاءمة المميزات التجريبية لـ تيار-جهد على العلاقة النظرية  التي تصف هذه المميزات في الإضاءة باستخدام برنامج OriginPro. لوحظ بشكل واضح أن عملية الملاءمة تحاكي القيم التجريبية إلى حد كبير وبالتالي تعطي قيم المتغيرات بشكل جيد وخاصة قيم التيار الضوئي وقيم مقاومة التسلسل ومقاومة التوازي اللتين تؤثران بشكل قوي على شكل المنحني عند المرور بمحور التيار وعند قيم كمون عالية.In this work was measured characteristics (current - voltage) for the solar cell (PIN) where the layer P and layer N of silicon amorphous . The layer (I) intrinsic it is made ​​from a mixture of silicon amorphous and microcrystalline hydrogenated in order to different illumination using a halogen bulb has  Power, as measured the intensity illumination incoming on cell by scale of the power it was Were obtained directly from the curves of the resulting characteristics on the basic variables for the solar cell: the short circuit current density , open-circuit voltage , fill factor , and efficiency of solar energy conversion (yield) . in order to obtain a solar cell variables such as saturation current  and ideality factor n and serial resistance , parallel resistance , current lighting  has fitting characteristics current-voltage experimental relationship theory that describes characteristics under illumination using the program OriginPro. Observed clearly that the process of fitting simulate experimental values significantly and thus she gives the values ​​of variables are particularly good values ​​of current optical and resistance values ​​serial resistance in parallel, which affect strongly on the shape of the curve when passing the axis of current, and when the values ​​of voltage is high.